Activation of central orexin/hypocretin neurons by dietary amino acids. - Karnani, M; Apergis-Schoute, J; Adamantidis, A; Jensen, LT; de Lecea, L; Fugger, L; Burdakov, D (2011)
Hypothalamic orexin/hypocretin (orx/hcrt) neurons regulate energy balance, wakefulness, and reward; their loss produces narcolepsy and weight gain. Glucose can lower the activity of orx/hcrt cells, but whether other dietary macronutrients have similar effects is unclear. We show that orx/hcrt cells are stimulated by nutritionally relevant mixtures of amino acids (AAs), both in brain slice patch-clamp experiments, and in c-Fos expression assays following central or peripheral administration of AAs to mice in vivo. Physiological mixtures of AAs electrically excited orx/hcrt cells through a dual mechanism involving inhibition of K(ATP) channels and activation of system-A amino acid transporters. Nonessential AAs were more potent in activating orx/hcrt cells than essential AAs. Moreover, the presence of physiological concentrations of AAs suppressed the glucose responses of orx/hcrt cells. These results suggest a new mechanism of hypothalamic integration of macronutrient signals and imply that orx/hcrt cells sense macronutrient balance, rather than net energy value, in extracellular fluid.